Communications Between Peripheral and the Brain-Resident Immune System in Neuronal Regeneration After Stroke - Liu, Fangxi; Cheng, Xi; Zhong, Shanshan; Liu, Chang; Jolkkonen, Jukka; Zhang, Xiuchun; Liang, Yifan; Liu, Zhouyang; Zhao, Chuansheng (Frontiers in Immunology, 2020)
Cerebral ischemia may cause irreversible neural network damage and result in functional deficits. Targeting neuronal repair after stroke potentiates the formation of new connections, which can be translated into a better functional outcome. Innate and adaptive immune responses in brain and the periphery triggered by ischemic damage participate in regulating neural repair after a stroke. Immune cells in the blood circulation and gut lymphatic tissues which have been shaped by immune components including gut microbiota and metabolites, can infiltrate into the ischemic brain, and once there, influence neuronal regeneration either directly or by modulating the properties of brain resident immune cells. Immune related signalings and metabolites from the gut microbiota can also directly alter the phenotypes of resident immune cells to promote neuronal regeneration. In this review, we discuss several potential mechanisms through which peripheral and brain resident immune components can cooperate to promote first the resolution of neuroinflammation and subsequently to improved neural regeneration and a better functional recovery. We propose that new insights into discovery of regulators targeting pro-regenerative process in this complex neuro-immune network may lead to novel strategies for neuronal regeneration.